2014
DOI: 10.1371/journal.pone.0086996
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Administration of Penicillamine Reduces Radiation Exposure in Critical Organs during 64Cu-ATSM Internal Radiotherapy: A Novel Strategy for Liver Protection

Abstract: Purpose 64Cu-diacetyl-bis (N 4-methylthiosemicarbazone) (64Cu-ATSM) is a promising theranostic agent that targets hypoxic regions in tumors related to malignant characteristics. Its diagnostic usefulness has been recognized in clinical studies. Internal radiotherapy (IRT) with 64Cu-ATSM is reportedly effective in preclinical studies; however, for clinical applications, improvements to reduce radiation exposure in non-target organs, particularly the liver, are required. We developed a strategy to reduce radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The mechanism of radiolabeled Cu-ATSM accumulation in hypoxic tumor area was currently under investigation but it was well-known than there was a high physiological accumulation of free 64 Cu in non-target organ and the liver was reported to be the principal dose-limiting organ ( 26 ). To reduce the liver absorbed dose, Yoshii et al showed that the use of a copper chelator like penicillamine could reduce liver absorbed dose (increase of free copper renal clearance) but have no effect on the Cu-ATSM tumor accumulation ( 27 ).…”
Section: Cu-atsm In Vivo Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of radiolabeled Cu-ATSM accumulation in hypoxic tumor area was currently under investigation but it was well-known than there was a high physiological accumulation of free 64 Cu in non-target organ and the liver was reported to be the principal dose-limiting organ ( 26 ). To reduce the liver absorbed dose, Yoshii et al showed that the use of a copper chelator like penicillamine could reduce liver absorbed dose (increase of free copper renal clearance) but have no effect on the Cu-ATSM tumor accumulation ( 27 ).…”
Section: Cu-atsm In Vivo Resultsmentioning
confidence: 99%
“…From this physiological metabolism of copper, it appears than free copper present a negative impact on the PET image information of 64 Cu-ATSM. Nevertheless, this impact could be decreased by the co-administration of d -penicillamine, which will permit to accelerate the elimination of free copper without impact on the 64 Cu-ATSM tumor fixation ( 27 ).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The mice were intravenously injected with 64 Cu-ATSM (37 MBq) or saline (day 21) and continued to be treated with bevacizumab (bevacizumab+ 64 Cu-ATSM group or bevacizumab alone). The dose of 64 Cu-ATSM (37 MBq) used in this study was decided based on toxicity and dosimetry analyses of previous studies, which demonstrated that the dosage results in no significant body weight loss and suggested not to administer radiation doses on the dose-limiting organs beyond the tolerance level [ 16 , 26 , 30 ]. For comparison, groups without bevacizumab treatment were also examined: 64 Cu-ATSM (37 MBq) on day 21 ( 64 Cu-ATSM alone-day 21 group); 64 Cu-ATSM (37 MBq) on day 7, on which day tumor size was similar to that in the bevacizumab-treated mice on day 21 ( 64 Cu-ATSM alone-day 7 group); saline instead of 64 Cu-ATSM (day 21) (control group).…”
Section: Resultsmentioning
confidence: 99%
“…Our in vivo treatment study showed that administration of 37 MBq of 64 Cu-ATSM had a therapeutic effect against bevacizumab-treated tumors without noticeably increased toxicity levels. We have previously demonstrated that 37 MBq of 64 Cu-ATSM was an appropriate dosage for treatment in mice, since it did not cause significant body weight loss and hematotoxicity [ 16 , 26 , 30 ]. In addition, we have estimated the human dosimetry of 64 Cu-ATSM based on the time-series biodistribution data in normal organs and tumors using mice bearing HT-29 tumors [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of penicillamine reduces intestinal copper accumulation during internal radiotherapy with 64 CuBTSC. 39 Thus, combined administration of penicillamine with CuGTSM may reduce copper overload in the ileum. In addition, dietary copper supplementation combined with zinc reduced the incidence and severity of diarrhea, which may applicable to CuGTSM treatment.…”
Section: Discussionmentioning
confidence: 99%